Inovasi Kurikulum dan Pembelajaran Pendidikan Singapore - Sholihah, Mar'atun; Kamil, Nurhusna; Nurramadani, Lilia; Saputri, Indri Dewi (Universitas Muhammadiyah Yogyakarta, 2024)
STEM, the acronym for Science, Technology, Engineering and Mathematics, is several groups of knowledge that are modified in one lesson. Nowadays, STEM learning has a special place in the hearts of every educator as an effort to improve 21st century skills. STEM learning can be combined with the provision of a makerspace. This article discussed the provision of STEM-based makerspaces in the world of education as learning curriculum innovations that can be implemented. This qualitative research applied a case study approach. The research sample consisted of 10 people in early childhood with an age range of 5-6 years. Interviews, observation, and documentation were methods used to make it easier to collect research data, while data analysis techniques were carried out by means of data triangulation starting from the stages of data collection, data reduction and data presentation. Based on the results of the research, information has been obtained that the application of STEM-based makerspaces in the world of education, especially at the preschool level, can stimulate children's development optimally. This is based on children's direct experience when carrying out activities that are more meaningful than just talking. Apart from that, the application of STEM-based makerspaces in the world of education is also believed to be able to increase children's interest and learning outcomes so that in the future, the application of STEM-based makerspaces should be increased further, especially in the 21st century